Korelasi Status Gizi dengan Kadar Saturasi Transferin pada Remaja Putri di SMK Baitul Hikmah Tempurejo - Melati Puspita Sari; Ririn Handayani; Ernawati Anggraeni; Yuni Handayani (Puslitbang Sinergis Asa Professional, 2025)
Adolescents are vulnerable to various nutritional problems, namely undernutrition and overnutrition as well as micronutrient deficiencies. East Java Province experienced an increase in the prevalence of severely thinness adolescents by 0.3% in 2023. A decrease in nutritional status caused by poor nutritional intake will result in iron micronutrient deficiency in the body. Indicators of iron deficiency include decreased serum iron levels and transferrin saturation. If the serum iron in the body decreases, there will be a disturbance in the establishment of erythrocytes, resulting in anemia. In iron deficiency conditions, transferrin saturation levels can reach <15%. This research investigates the correlation of nutritional status with transferrin saturation levels in adolescent girls at SMK Baitul Hikmah. This research applied analytic correlation with cross-sectional design. The research population was 74 adolescent girls. The sampling technique used Accidental Sampling so that a sample of 21 respondents who met the inclusion criteria was obtained. The analysis used was univariate and bivariate with Chi Square statistical test. The results showed that the nutritional status of the majority of respondents was severely thinness, 10 people (47.6%) and the respondents' transferrin saturation levels were mostly normal, 15 people (71.4%). The results of the analysis showed no correlation between nutritional status and transferrin saturation levels in adolescent girls at SMK Baitul Hikmah, p value 0.545 (>0.05). Enterprises that can be implemented by adolescent girls to get transferrin saturation levels and normal nutritional status include increasing food intake by fulfilling balanced nutrition, especially meeting iron needs. Perform laboratory examinations in the context of screening to establish a diagnosis, as well as monitor the success of therapy.